Development of a robotic system for autonomous agriculture - Sim, Ryan Hao Boon (Nanyang Technological University, 2024)
This thesis talks about the usage of a robot dog to help automate farming. It is focused on implementing fruit detection onto the robotic arm attached to the robot dog, further implementation where a string of commands are run to allow the robot dog move point to point and harvest the crop are still underway.